PENGARUH LINGKUNGAN SEKOLAH TERHADAP KESEJAHTERAAN EMOSIONAL DAN PRESTASI AKADEMIK - Hajrani; Kamaruddin, Syamsu A; Mustafa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
School environment is a crucial determinant in supporting students’ emotional well-being and academic achievement. This study aims to analyze the influence of various aspects of the school environment including school climate, physical conditions, social relationships, and the implementation of social-emotional learning (SEL) programson students’ emotional well-being and academic performance. Using a narrative literature review approach, the study synthesizes key theories and empirical findings from international and local research. The review shows that a positive school environment consistently contributes to improved emotional well-being among students through mechanisms such as enhanced sense of safety, reduced stress, greater sense of belonging, and better teacher-student relationships. Adequate physical conditionssuch as lighting, ventilation, and classroom comfortare found to enhance focus, motivation, and engagement in learning. Furthermore, SEL programs play a significant role in strengthening emotional regulation skills, empathy, and social interaction, which then impact academic performance. Empirical evidence from prior studies indicates that emotional well-being acts as a critical mediator between the school environment and academic achievement; students with high well-being are more likely to exhibit better motivation, attendance, and persistence. Therefore, strengthening the school environment through infrastructural improvements, enhanced quality of social relationships, and implementation of SEL programs is a key strategy to sustainably improve students’ emotional well-being and academic achievement. This review provides important implications for teachers, school principals, and policymakers in designing holistic, evidence-based interventions.